2021
DOI: 10.3389/fsurg.2021.612813
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Stage Migration in Radical Prostatectomy—A Sustaining Phenomenon

Abstract: Objective: To investigate temporal trends in prostate cancer (PCa) radical prostatectomy (RP) candidates.Materials and Methods: Patients who underwent RP for PCa between January 2014 and December 2019 were identified form our institutional database. Trend analysis and logistic regression models assessed RP trends after stratification of PCa patients according to D'Amico classification and Gleason score. Patients with neoadjuvant androgen deprivation or radiotherapy prior to RP were excluded from the analysis.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
2
14
0
3
Order By: Relevance
“…First, patient and RC-related characteristics, as well as outcome of interests were tabulated following stratification according to NAC status. Second, the estimated annual percentage change (EAPC) analyses were generated relying on the least squares linear regression methodology, as previously described [ 23 , 24 ]. EAPC analyses were weighted according to NIS methodology [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, patient and RC-related characteristics, as well as outcome of interests were tabulated following stratification according to NAC status. Second, the estimated annual percentage change (EAPC) analyses were generated relying on the least squares linear regression methodology, as previously described [ 23 , 24 ]. EAPC analyses were weighted according to NIS methodology [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, broad PSA testing was questioned and subsequently, a declining incidence of PCa was observed in the latest years, also within Germany. [2][3][4] On the other hand, when limiting PSA tests, the potential for inverse stage migration for PCa is evident. 5,6 In a recent report by Boehm et al, 7 as well as within another report by Van den Bergh et al, 8 the continuing trend of inverse stage and grade migration in PCa patients was confirmed, not only in Germany, but also throughout Europe.…”
Section: Introductionmentioning
confidence: 99%
“…This was specifically important when considering invasive treatment options, such as radical prostatectomy (RP). For this reason, broad PSA testing was questioned and subsequently, a declining incidence of PCa was observed in the latest years, also within Germany 2–4 . On the other hand, when limiting PSA tests, the potential for inverse stage migration for PCa is evident 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several hypotheses may be proposed to explain the differences between overall survival between contemporary and historical patients. Customarily, the differences between contemporary and historical patients consist of a more favorable stage, age, and other cancer characteristics that invariably result in better overall survival 19,20 . Our analyses demonstrated that this effect did not account for the chemotherapy benefit, as outlined above.…”
Section: Discussionmentioning
confidence: 67%